Clinical Presentation, Treatment Outcomes, and Resistance-related Factors in South American Women with Low-risk Postmolar Gestational Trophoblastic Neoplasia - Ramírez, Luz Angela Correa [UNESP]; Maestá, Izildinha [UNESP]; Bianconi, María Inés; Jankilevich, Gustavo; Otero, Silvina; Mejía, Carlos Raúl Villegas; Cortés-Charry, Rafael; Elias, Kevin M.; Horowitz, Neil S.; Seckl, Michael; Berkowitz, Ross S. (Federação das Associações de Ginecologia e Obstetrícia, 2022)
Objective â There are few multinational studies on gestational trophoblastic neoplasia (GTN) treatment outcomes in South America. The purpose of this study was to assess the clinical presentation, treatment outcomes, and factors associated with chemoresistance in low-risk postmolar GTN treated with first-line single-Agent chemotherapy in three South American centers. Methods â Multicentric, historical cohort study including women with International Federation of Gynecology and Obstetrics (FIGO)-staged low-risk postmolar GTN attending centers in Argentina, Brazil, and Colombia between 1990 and 2014. Data were obtained on patient characteristics, disease presentation, and treatment response. Logistic regression was used to assess the relationship between clinical factors and resistance to first-line single-Agent treatment. A multivariate analysis of the clinical factors significant in univariate analysis was performed. Results â A total of 163 women with low-risk GTN were included in the analysis. The overall rate of complete response to first-line chemotherapy was 80% (130/163). The rates of complete response to methotrexate or actinomycin-D as first-line treatment, and actinomycin-D as second-line treatment postmethotrexate failure were 79% (125/157), 83% (â š), and 70% (23/33), respectively. Switching to second-line treatment due to chemoresistance occurred in 20.2% of cases (33/163). The multivariate analysis demonstrated that patients with a 5 to 6 FIGO risk score were 4.2-fold more likely to develop resistance to first-line single-Agent treatment (p = 0.019). Conclusion â 1) At presentation, most women showed clinical characteristics favorable to a good outcome, 2) the overall rate of sustained complete remission after first-line single-Agent treatment was comparable to that observed in developed countries, 3) a FIGO risk score of 5 or 6 is associated with development of resistance to first-line single-Agent chemotherapy.
Apresentação clínica, resultados do tratamento e fatores relacionados à resistência em mulheres sul-Americanas com neoplasia trofoblástica gestacional pós-molar de baixo risco
Keywords: chemotherapy; low-risk gestational trophoblastic neoplasia; molar pregnancy; resistance-related factors; South America